“completación dual concéntrica con bombas eléctricas sumergibles de un pozo en el oriente ecuatoriano revestido con casing de 9-5/8” - Romero Pinargote, Cesar (2010)
This paper aims to show the design of a dual completion concentric with electric submersible pumps, pipe coating with 9-5/8''to the well ESPOL CR-AG. Having as main objective the design of a completion, considering the production of the field, lining the hole, the arrangement of production equipment and the number of producing areas, in which to reduce operational problems usually occur. The first part briefly to pose a dual completion, the various accessories of the same, and electric submersible equipment we'll use in our well. We proceed to show the design of our dual completion-BES BES concentric with its own technical analysis and assembly process of each of its parts. Shown are the results of calculations made for the completion depths, as well as the relevant economic analysis, conclusions and recommendations so that we get to have a clear idea of the completion design for a well in eastern Ecuador raised in this article.